Electrospinning and crosslinking of polyvinyl alcohol/chitosan composite nanofiber for transdermal drug delivery. Issue 6 (2nd June 2017) - Cui, Zhixiang; Zheng, Zifeng; Lin, Luyin; Si, Junhui; Wang, Qianting; Peng, Xiangfang; Chen, Wenzhe
Abstract: The drug‐loaded polyvinyl alcohol (PVA)/chitosan (CS) composite nanofibers intended to be used as matrix for transdermal drug delivery were fabricated by electrospinning, and then crosslinked through glulataraldehyde (GA). The morphology, chemical structure, thermal behavior, mechanical properties, hydrophilicity and drug release properties of drug‐loaded PVA/CS composite nanofibers before and after crosslinking were characterized. The results showed that the morphology of PVA/CS composite nanofibers was not been destroyed in both crosslinking and in vitro drug release process. The Young's modulus, tensile strength, thermal properties and hydrophobicity of crosslinked PVA/CS composite nanofibers significantly increased in comparison with those of PVA/CS (without crosslinking) due to the formation of crosslinking network structure. In vitro release studies showed that crosslinked PVA/CS composite nanofibers had lower drug release rate and smaller amount of drug burst release than that of PVA/CS. According to release exponent " n ", the release of ampicillin sodium from crosslinked PVA/CS composite nanofibers fit to the Fickian diffusion mechanism. Those results demonstrate the potential utilization of crosslinked PVA/CS composite nanofibers as a transdermal drug delivery system.